BOOK REVIEW: CRITICAL THINKING - DIEORDITSA, Taiana; TOLMACHOV, Volodimir (Physical and Mathematical Education, 2024)
«Critical Thinking» by J. Haber provides an overview of critical thinking's history, the skills required for it, and current pedagogical efforts to develop it.
Keywords: critical thinking; logic; rhetoric; argumentation; information literacy